Hydrothermally synthesised porous NiAl-LDH as an efficient pseudocapacitive material in asymmetric supercapacitors - Raman Duddi; Shivani; Shobhna Dhiman; Arun Kumar Singh; Navpreet Kamboj; Sanjeev Kumar (Hybrid Advances)
Layered double hydroxides (LDH) have gained recognition as leading cathode materials, attributed to their unique properties like high durability, cost-effectiveness, hierarchical architecture, extensive surface area, large pore volume, and rapid ion diffusion kinetics. The composition and structural design of these materials hold significant importance in judging the performance of energy storage devices. In this study, we have developed a porous structure of NiAl-LDH using a single-step hydrothermal technique. The phase purity, bonding environment, and structural and morphological properties of the NiAl-LDH were analysed using XRD, FTIR, SEM, EDAX, BET, XPS and HRTEM techniques. The synthesised NiAl-LDH electrode material exhibited a high BET surface area ∼117.4 m2 g−1, contributing significantly to its enhanced electrochemical performance in supercapacitor applications. The NiAl-LDH@ITO glass nanostructure demonstrating a significantly enhanced specific capacitance of 589.3 F g−1 at 1 A g−1. When the as-prepared electrode is integrated with a commercial activated carbon (AC) to form a hybrid asymmetric supercapacitor (ASC) operating in 1 M KOH electrolyte, it delivers specific capacitance of 923 F g−1. The ASC achieves a peak power density of 5200 W kg⁻1, an energy density of 216 Wh kg⁻1, and a cell voltage 1.3 V. Notably, after 10,000 charge/discharge cycles at low current densities, it retains 91 % of its initial capacitance. The superior storage properties of the NiAl-LDH electrode make it a suitable candidate for future generation energy storage applications.